Houses Built on Sand Effects of Exemplar Stability on Susceptibility to Attitude Change. (article). - Lord, Charles G.
Attitude representation theory (C.G. Lord & M. R. Lepper, 1999) explains both attitude-behavior consistency and attitude change with the same principles. when individuals respond evaluatively to an attitude and combine assumptions about the attitude object with perception of the immediate situation. The assumption activated can vary across time, even without additional information . Previous research has shown that individuals activate exemplars when answering attitude questions, attitude reports vary with the valence of the assumptions activated, and activating differently liked exemplars reduces attitude -behavior consistency. The present research completed study of the theoretical of exemplar stability by showing that individuals with temporally unstable exemplars whether spontaneous (Experiment 1) or manipulated (Experiment 2 and 3), are more susceptible to subsequent attitude change that are individuals with stable exemplars. -- (from the author).